2012
DOI: 10.14773/cst.2012.11.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of Continuous Galvanization-compatible Martensitic Steel

Abstract: The development of martensitic grades which can be processed in continuous galvanizing lines requires the reduction of the oxides formed on the steel during the hot dip process. This reduction mechanism was investigated in detail by means of High Resolution Transmission Electron Microscopy (HR-TEM) of cross-sectional samples. Annealing of a martensitic steel in a 10% H2 + N2 atmosphere with the dew point of-35 ℃ resulted in the formation of a thin c-xMnO.SiO2 (x>1) oxide film and amorphous a-xMnO.SiO2 oxide pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[21][22][23][24] However, Gong found that Mn-Si mixed oxides can be reduced by dissolved Al during dipping so that the stable oxide, MnAl 2 O 4 forms. 25 However, because there are no other similar findings, it still needs an in-depth investigation.…”
Section: Cr Oxidementioning
confidence: 99%
“…[21][22][23][24] However, Gong found that Mn-Si mixed oxides can be reduced by dissolved Al during dipping so that the stable oxide, MnAl 2 O 4 forms. 25 However, because there are no other similar findings, it still needs an in-depth investigation.…”
Section: Cr Oxidementioning
confidence: 99%